Role And Effectiveness Of WIKI Technology To Support Knowledge Management In The Academic Environment - Nejadmahani, Mohammad Falahat (2007)
The purpose of this study is to examine the students needs and requirements from the MBA course and evaluate Wiki as a Knowledge Management System (KMS). This is to facilitate and fulfill the demands based on accessibility and progressive learning.